2005
DOI: 10.1021/jo050792l
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Aldol Reaction Based on Titanium Enolates from (S)-1-Benzyloxy-2-methyl-3-pentanone

Abstract: Alternative titanium-mediated aldol procedures based on several protected beta-hydroxy ethyl ketones have been surveyed. Eventually, enolization of (S)-1-benzyloxy-2-methyl-3-pentanone (1) with (i-PrO)TiCl3/i-Pr2NEt provided a very reactive enolate that afforded the corresponding 2,4-syn-4,5-syn aldol adducts in high yields and diastereomeric ratios with a broad range of aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Table 6.3, entries 12-28). The latter are more commonly employed, in part because of the increased expense and technical challenge associated with the use of Sn(II) enolates [75]. Judging from the results obtained with Paterson's dipropionate equivalent 20 (Scheme 6.14 and Table 6.3), it can be anticipated that reactions of (S)-syn-(Z)-8a (e.g., ML n = SnOTf) with (S)-12 should be ''matched'' and give the 49ssa adduct.…”
Section: Tin Enolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6.3, entries 12-28). The latter are more commonly employed, in part because of the increased expense and technical challenge associated with the use of Sn(II) enolates [75]. Judging from the results obtained with Paterson's dipropionate equivalent 20 (Scheme 6.14 and Table 6.3), it can be anticipated that reactions of (S)-syn-(Z)-8a (e.g., ML n = SnOTf) with (S)-12 should be ''matched'' and give the 49ssa adduct.…”
Section: Tin Enolatesmentioning
confidence: 99%
“…reactions of the Ti(IV) (Z)-enolate (Z)-21a (ML n = TiCl 3 ), prepared by reaction of 20a with TiCl 4 /Et 3 N, were much less stereoselective [73c],[75], perhaps because of less favorable intramolecular coordination in the Ti(IV) enolate compared to the Sn(II) enolate. Interestingly, Urpí et al[75] found that the analogous Ti(IV) enolate (Z)-21a (ML n = Ti(Oi-Pr)Cl 2 ), prepared by reaction of 20a with Ti(Oi-Pr)Cl 3 /Et 3 N, showed excellent stereoselectivity.…”
mentioning
confidence: 99%
“…The authors used different titanium reagents and evaluated the selectivity of the aldol reactions between ethyl ketones ent- 15,11, and 20 and isobutyraldehyde (2). The best results were obtained for ethyl ketone ent-15 (R = Bn) using Ti(iPrO)Cl 3 as the Lewis acid (Table 5.1, entry 3) [19].…”
Section: 4-asymmetric Induction Using α-Alkyl Ketonesmentioning
confidence: 99%
“…The partially matched reaction involving aldehyde ent-253 (case C) was the most interesting of the stereochemical permutations because the enolate facial bias established a matched relationship with the aldehyde β-heteroatom and a mismatched relationship with respect to the normally dominant aldehyde α-stereocenter. Felkin control was overridden in this reaction to produce the anti-Felkin aldol adduct 331 (dr = 81 :19). It is difficult to explain the stereochemical outcome of this reaction without invoking the β-heteroatom as a stereochemical determinant.…”
mentioning
confidence: 99%
See 1 more Smart Citation